(untitled) (Research, Society and Development, 2021)
Coronaviruses are simple, positive, and unsegmented RNA viruses, in addition to having one of the largest genomes among RNA viruses. Discussions around these viruses resurfaced with the appearance of a new coronavirus, SARS-CoV-2, in the city of Wuhan, China, in late 2019. In March 2020, the World Health Organization declared the outbreak a pandemic, and the new virus drew attention for its high transmissibility, intrinsic characteristics and social impact. Therefore, the present study aims to outline the epidemiological characteristics that involve mortality from SARS-CoV-2 in the municipality of Vitória da Conquista, Bahia, Brazil. A cross-sectional, descriptive study with a quantitative approach was carried out. All cases of deaths from Covid-19 that occurred between April 2020 and August 2021 were analyzed. As a data collection instrument, electronic medical records integrated in the Covid-19 Monitoring System of the municipality were used. During the period evaluated, 33,539 data from patients were analyzed, of which 610 progressed to death. The profile of death by Covid-19 in the city is formed mostly by male patients, aged over 60 years. Symptoms: 94% lower oxygen saturation, respiratory difficulties/changes and cyanosis, together with the presence of comorbidities, correlated as factors for greater chances of death in the population studied. The need for the development of public policies aimed at the prevention and care of patients with potential risk of death is evidenced.